PROBLEMS OF THE INVESTMENT CLIMATE OF THE ARCTIC ZONE - O. Krasulina (Модернизация, инновация, развитие)
The article focuses on general characteristics of the investment climate of the Arctic zone of the Russian Federation, analyses its structure (through the example of the investment climate of certain arctic regions), and suggests potential areas of focus in the improvement work.